Primer hallazgo de Dermatobia hominis (“ura”) (Linnaeus f., 1781) (Diptera: Oestridae) en bovinos del este de Salta, Argentina - Rosetto, Cristina Beatriz (2025)
The presence of cattle with lesions of furunculous myiasis caused by Dermatobia hominis ("ura") (Díptera: Oestridae) is described in an extensive breeding herd of 100 cattle located on the right (or south) bank of the Bermejo River (Rivadavia department, Salta province). Only four adult cattle (4%) were observed with skin lesions, mostly on the neck table. This parasitic infection was not previously known to cattle ranchers in the area. It is postulated that D. hominis, endemic to northeastern Argentina, has expanded its range, now reaching the northwest of the country.